Required Structures for Family Physician Program to Achieving Service Quality Dimensions in Primary Health Care: a systematic review - Ali Reza Heidarian Naeini; Ghahraman Mahmoodi Alemi; Jamshid Yazdani Charati (Tehran University of Medical Sciences, 2021)
Background and Aim: In recent years, the family physician plan has been implemented as a main strategy of health system in Iran. Therefore, the necessity to reform organizational structure based on experiences of other countries is felt more than before. The aim of this study was to explore required structures of Family Physician Program to achieve service quality dimensions in Primary Health care through analyzing country experiences. Materials and Methods: This study was a systematic review. All relevant databases were searched using appropriate search strategies and keywords (Family Physicians, Primary Health Hare, Quality of Care). To evaluate the quality of selected papers, CASP tool was applied by 4 experts, and their choices were discussed to reach a final decision. Results: In order to achieve the quality of services in the field of family medicine, based on the findings of this study, eight important executive structures must be considered. These structures are: Organizational and managerial structures, including health system governance, Support  mechanisms and referral system, Systematic communication platform, Electronic health services, Service delivery processes,Insurance structure, Supervisory and control structure including financial control mechanisms, competitive control and quantitative control, Payment structure, quantitative and qualitative development structure of service providers, Quality structure that includes the definition and evaluation of quality and accountability mechanisms as well as incentive mechanisms for service quality, Support structure including insurance support, classified support for specific groups, and finally, the cultural structure in the two areas of culture building of the referral system and strengthening the position of family physicians. Conclusion: Quality improvement in primary health care requires attention to executive structures. Use of executive experiences of other countries will be useful in achievement of quality health care in family physician system.